Strategies for creating village identity symbols using street art tactics:: Staro Zhelezare, Bulgaria - Piriankov, Katarzyna (Street Art & Urban Creativity, 2018)
Over the last few years, various projects in the village of Staro Zhelezare have been undertaken aiming to involve and collaborate with the residents in order to directly improve the quality of social life and the image of the depressed neighbourhood. The purpose of the paper is to examine how different strategies of specific bottom-up activities in a public space address various problems in such a small community. Following the Fourth Street Art Festival in Staro Zhelezare, it is clear that the project has proved to be a considerable success in developing a strong visual identity that has helped to shape the image of the village and introduced resilience features. This paper addresses the problem of how to increase awareness of the inexpensive yet relatively accessible possibilities and potential of public spaces in small, economically depressed localities.